Integrated process development of a reactive extraction concept for itaconic acid and application to a real fermentation broth. Issue 7 (27th March 2017) - Gorden, Jannick; Geiser, Elena; Wierckx, Nick; Blank, Lars M.; Zeiner, Tim; Brandenbusch, Christoph
Abstract : Itaconic acid (IA) has a high potential to be used as a bio‐based platform chemical and its biocatalytic production via fermentation has significantly improved within the last decade. Additionally downstream processing using reactive extraction (RE) was described, potentially enabling a more efficient sustainable bioprocess producing IA. The bottleneck to overcome is the connection of up‐ and downstream processing, caused by lack of biocompatibility of the RE systems and direct application to fermentation broth. Within this study, a biocompatible RE system for IA is defined (pH dependency, extraction mechanism) and used for direct application to a fermentation broth. By optimizing the biocatalyst, the production medium, and the extraction system in an integrated approach, it was possible to define critical parameters that enabled a tuning of the overall bioprocess. With an extraction yield of Y IA  = 0.80 ± 0.03, IA could be produced as sole carboxylic acid ( b IA, 0 aq  = 0.490 mol/kg aq ) using a RE system consisting of ethyl oleate as organic solvent and tri‐ n ‐octylamine as extractant ( b T - C 8 org  = 0.6 mol/kg org ). This work is a proof of concept and demonstrates that by joint consideration of up‐ and downstream processing, optimized bioprocesses can be developed.